Breaking (with) the System: exodus as Resistance? - Buuren, Jelle van (Perspectives on terrorism, 2023)
Anti-government extremism is frequently characterised by its violent potential such as harassment and violence against politicians, government officials, experts, and journalists. Although understandable from the perspective of radicalisation and terrorism scholars, another tendency within the fluid anti-government movements is sometimes overlooked: ‘internal migration’, in which parallel enclaves are created in order to escape the perceived repressive order of the system. It signals attempts to build ‘free zones’ within society on the base of a discourse denying the legitimacy of the political order. In this article the author will assess whether or not exodus as a distinctive, usually nonviolent form of anti-government politics should be understood as relatively harmless or as the forerunners of more confrontational practices, such as deliberately undermining the liberal order by fuelling anti-system sentiments or preparing for resistance in a later stage, that in the long term could have security implications. This article will propose an initial, tentative analytical model to answer these questions, and then the Dutch political party Forum for Democracy will be used as a case to demonstrate the argument and explore the strengths and limitations of the proposed model.